Spatial variation in the use of reproductive health services over time: a decomposition analysis - Gordon Abekah-Nkrumah (BMC, 2018)
Abstract Background The paper argues that several Sub-Saharan African countries have recorded marked improvements in the use of reproductive health services. However, the literature has hardly highlighted such progress and the factors responsible for them. The current study uses Ghana as a case to examine progress in the consumption of reproductive health services over the last two decades and the factors responsible for such progress. Methods The study uses two rounds (1998 and 2014) of Demographic and Health Survey data from Ghana. Standard frequencies, a logit model and decomposition of the coefficients of the logit model (i.e. Oaxaca-type decomposition) was employed to examine changes in the use of reproductive health services (4+ antenatal visits and skilled attendance at birth) at national and sub-national levels (i.e the four ecological zones of Ghana) between 1998 and 2014 as well as factors explaining observed spatial changes between the two periods. Results Descriptive results suggest that the highest level of improvement occurred in resource-poor zones (i.e. northern belt followed by the southern belt) compared to the middle belt and Greater Accra, where access to resources and infrastructure is relatively better. Results from Oaxaca-type decomposition also suggest that women and partner's education, household wealth and availability and accessibility to health facilities are the key factors explaining spatial variation in reproductive health service consumption over the two periods. Most importantly, the marginal efficiency of investment in women and partner's education and access to health services were highest in the two resource poor zones. Conclusion There is the need to target resource poor settings with existing or new pro-poor reproductive health interventions. Specifically, the northern and southern zones where the key drivers of education and availability of health facilities are the lowest, will be key to further improvements in the consumption of reproductive health services in Ghana.